PERBANDINGAN HASIL BELAJAR IPS TERPADU MENGGUNAKAN MEDIA ICT DAN MEDIA TRADISIONAL - Paulus Tendy; I Komang Winatha; Tedi Rusman (FKIP Unila, 2015)
This research aims to know the difference of students learning results in IPS Terpadu subject and the effectiveness between the use of ICT media and traditional media in IPS Terpadu subject at the seventh grade students of SMP Negeri 23 Bandar Lampung.This research is an experimental research method with a comparative approach. The population in this research were 153 students and the sample was two classes which divided into 25 students of experiment class and 23 students of control class. The sample was taken by using cluster sampling. The data were collected by using observation, documentation and test. The data were analyzed by using T-test Two Sample Independent and Formula of N-Gain. The result of this research showed that: (1) The average of students learning results in IPS Terpadu subject who taught by using ICT is higher than who taught by using traditional media, (2) There is a difference of effectiveness between the use of ICT media and traditional media.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar IPS Terpadu siswa dan perbedaan efektivitas antara media ICT dengan media tradisional pada mata pelajaran IPS Terpadu siswa kelas VII di SMP Negeri 23 Bandar Lampung. Penelitian ini menggunakan metode penelitian eksperimen dengan pendekatan komparatif. Populasi dalam penelelitian ini berjumlah 153 siswa dan sampel sebanyak dua kelas yang terdiri dari 25 siswa kelas eksperimen dan 23 siswa kelas kontrol. Sampel diambil menggunakan cluster sampling. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan tes. Analisis data menggunakan T-test Dua Sampel Independen dan rumus N-Gain. Hasil penelitian ini menunjukkan bahwa: (1) Rata-rata hasil belajar IPS Terpadu siswa ada yang diajar menggunakan media ICT lebih tinggi dibandingkan dengan siswa yang diajar menggunakan media tradisional, (2) Ada perbedaan efektifitas antara media ICT dan media tradisional.Kata kunci : hasil belajar, ICT, tradisional.